13.2k views
5 votes
Which expression is equivalent to (2mn)^4/6m^-3n^-2? Assume .m=0,n=0

8m^7n^6/3
10m^7n^6/3
8m^16n^12/3
m^4n^6/3

2 Answers

4 votes
8m^7n^6
------------
3
User Gdso
by
5.7k points
3 votes

Given expression:
((2mn)^4)/(6m^(-3)n^(-2)).


\mathrm{Apply\:exponent\:rule}:\quad \left(ab\right)^c=a^cb^c


\left(2mn\right)^4:\quad 2^4m^4n^4


=(2^4m^4n^4)/(6m^(-3)n^(-2))


=(2^4m^4n^4)/(2\cdot \:3m^(-3)n^(-2))


=(2^3m^4n^4)/(3m^(-3)n^(-2))


\mathrm{Apply\:exponent\:rule}:\quad (x^a)/(x^b)\:=\:x^(a-b)


(m^4)/(m^(-3))=m^(4-\left(-3\right))=m^7


=(2^3m^7n^4)/(3n^(-2))


(n^4)/(n^(-2))=n^(4-\left(-2\right))=n^6


=(2^3m^7n^6)/(3)


=(8m^7n^6)/(3)\

Therefore, correct option is first option
(8m^7n^6)/(3).

User Gulam
by
5.2k points